Metabolic profiles alteration of Southern Thailand traditional sweet pickled mango during the production process - Indrati, Niken; Phonsatta, Natthaporn; Poungsombat, Patcha; Khoomrung, Sakda; Sumpavapol, Punnanee; Panya, Atikorn (Frontiers in Nutrition, 2022)
Sweet pickled mango named Ma-Muang Bao Chae-Im (MBC), a delicacy from the Southern part of Thailand, has unique aroma and taste. The employed immersion processes (brining1, brining2, and immersion in hypertonic sugar solution, sequentially) in MBC production process brings changes to the unripe mango, which indicate the occurrence of metabolic profiles alteration during the production process. This occurrence was never been explored. Thus, this study investigated metabolic profile alteration during the MBC production process. Untargeted metabolomics profiling method was used to reveal the changes of volatile and non-volatile metabolites. Headspace solid phase micro-extraction tandem with gas chromatography quadrupole time of flight (GC/QTOF) was employed for the volatile analysis, while metabolites derivatization for non-volatile analysis. In conclusion, a total of 82 volatile and 41 non-volatile metabolites were identified during the production process. Terpenes, terpenoids, several non-volatile organic acids, and sugars were the major mango metabolites that presented throughout the process. Gamma aminobutyric acid (GABA) was only observed during the brining processes, which suggested the microorganism's stress response mechanism to an acidic environment and high chloride ions in brine. Esters and alcohols were abundant during the last immersion process, which had an important role in MBC flavor characteristic. The knowledge of metabolites development during MBC production process would be beneficial for product development and optimization.